ETIKA BISNIS SEBAGAI LANDASAN PELAKSANAAN CORPORATE SOCIAL RESPONSIBILITY (CSR) PERUSAHAAN INDONESIA - Charlene Victoria; Deby Jocelyn; Florence; Regina Ongko; Nathasya Christie; Susan Grace V Nainggolan (Jurnal Riset Multidisiplin Edukasi, 2025)
This study aims to examine the role of business ethics as the basis for implementing corporate social responsibility in companies in Indonesia, explain how it is applied in practice, and identify the challenges faced. The research uses a qualitative descriptive method with a literature study approach. Data was obtained from various relevant written sources and analyzed using content analysis techniques through a process of theme grouping and conclusion drawing. The results of the study indicate that business ethics serve as moral guidelines that direct companies in carrying out their social responsibilities in a responsible and sustainable manner. The application of business ethics encourages corporate social responsibility to not only be a formality, but to be integrated with business strategies and provide tangible benefits to society and the environment. However, the implementation of social responsibility based on business ethics still faces challenges, such as a low understanding of ethical values, limited resources, and a lack of consistency in its application.